Intrauterine Growth Restriction Induces Adulthood Chronic Metabolic Disorder in Cardiac and Skeletal Muscles - Li, Ping; He, Lewei; Lan, Yue; Fang, Jie; Fan, Zhenxin; Li, Yifei (Frontiers in Nutrition, 2022)
Objective Although population based studies of intrauterine growth restriction (IUGR) demonstrated a series of postnatal complications, and several studies identified that IUGR could definitely cause cardiac and skeletal muscle dysfunction of metabolism at perinatal period and early life. However, it is still unknown if such metabolic alternation would remain a long term or not. And whether normal protein diet administration postnatally would protect the IUGR offsprings undergoing a “catch-up” growth and be able to reverse the premature metabolic. Methods We established an IUGR rat model by pregnant low protein diet. And the developmental phenotypes had been carefully recorded. Myocardium and skeletoal muscle had been collected to undergo RNA-seq. Results According to a series comparisons of transcriptome among various developmental process, programed metabolic dysfunction and chronic inflammation activity had been identified by transcriptome sequencing in IUGR offsprings even such rats presented a normal developmental curve or bodyweight after normal postnatal diet feeding. Conclusion The data revealed a significant effect of IUGR on the long-term adulthood cardiovascular complications, even they presented well nutrition condition. So that, the fetal stage adverse events would encode the life long disease risk, which could hide in young age. This study remaindered the research of long-term molecular changes is important and only nutrition improvement would not totally reverse the damaging of IUGR.